Velocity-space sensitivity and tomography of scintillator-based fast-ion loss detectors. (23rd August 2018) - Galdon-Quiroga, J; Garcia-Munoz, M; Salewski, M; Jacobsen, A S; Sanchis-Sanchez, L; Rodriguez-Ramos, M; Ayllon-Guerola, J; Garcia-Lopez, J; Gonzalez-Martin, J; Jimenez-Ramos, M C; Rivero-Rodriguez, J F; Viezzer, E
Abstract: A simple model for the instrument function of scintillator-based fast-ion loss detectors (FILD) has been developed which accounts for the orbit trajectories in the 3D detector geometry and for the scintillator response. It allows us to produce synthetic FILD signals for a direct comparison between experiments and simulations. The model uses a weight function formalism to relate the velocity-space distribution of fast-ion losses reaching the detector pinhole to the scintillator pattern obtained experimentally, which can be understood as a distortion of the velocity-space distribution due to the finite resolution of the system. The tool allows us to recover the undistorted velocity-space distribution of the absolute flux of fast-ion losses reaching the detector pinhole from an experimental measurement using tomographic inversion methods, which can reveal additional details of the velocity-space distribution of the lost ions.